Multiple‐stressor effects on leaf litter decomposition and fungal decomposers in agricultural streams contrast between litter species. (23rd November 2015) - Bruder, Andreas; Salis, Romana K.; McHugh, Nicola J.; Matthaei, Christoph D.
Summary: Agricultural land use commonly exerts multiple stressors on the functioning of stream ecosystems, including leaf litter decomposition and the utilization of this resource in stream food webs. If stressors interact, their cumulative effects on biotic responses cannot be predicted from knowledge of individual stressor effects, posing challenges for management and restoration of ecosystems. We examined the individual and interactive effects of four common agricultural stressors and the role of litter quality on leaf litter decomposition and fungal decomposers. In 128 outdoor, flow‐through mesocosms, we manipulated levels of nutrients, a nitrification inhibitor (dicyandiamide), deposited fine sediment and flow velocity. Interactions among these stressors can ensue because, for instance, they jointly affect physicochemical conditions around leaf litter colonized by fungi such as concentrations of dissolved oxygen and nutrients. The two litter species used, deciduous birch and evergreen mahoe, showed contrasting decomposition dynamics, and these differences influenced their response to stressors. Fungi were important for birch litter decomposition but played a minor role for mahoe. Overall, flow velocity reduction and deposited fine sediment had the strongest, mainly negative effects on fungi and litter decomposition, probably as a consequence of reductions in dissolved oxygen available to fungi. However, fine sediment substantially increased mahoe litter mass loss, pointing at fungi‐independent processes being relevant for its decomposition. Although interactions among stressors were uncommon, they showed effects of the same magnitude as stressor main effects. Potential mechanisms underlying interactions included reductions in dissolved oxygen and changes in microbial community composition. Knowledge of the effects of multiple agricultural stressors and of litter quality on litter decomposition and litter‐associated fungi is crucial for management of forested riparian corridors, which have been shown to efficiently mitigate impacts of agricultural stressors on streams. The contrasting responses of the litter species used in our study warrant consideration of species composition of the riparian vegetation. Abstract : Lay Summary